Pengembangan Kreativitas Pembuatan Bouquet di Kalangan Ibu Rumah Tangga di Desa Cibogo - Novita Giarti Saputri; Azizah, Rifa Noer; Hidayah, Shofi Badriatul (PROCEEDINGS UIN SUNAN GUNUNG DJATI BANDUNG, 2024)
The skill of making flower bouquets and snack bouquets is very useful, especially for mothers and young women. They can use these skills to decorate their homes or develop them as home business units. This service activity aims to increase the insight of housewives in Cibogo Village about how to make flower bouquets from existing materials and foam as well as snack bouquets from light cakes and children's snacks. Activities are carried out to increase their insight and skills so that they can be used for household needs or developed as a small business unit. Several RT 14 women were involved in this activity. They learn the procedures for making flower bouquets from existing fabric and snack bouquets actively and continue with direct practice in making works. It is hoped that participants can utilize their knowledge to develop their talents and interests and home business units.